PERAN INDONESIA DALAM MEWUJUDKAN SUSTAINABLE DEVELOPMENT GOALS TUJUAN 14 KHUSUSNYA DALAM MENANGGULANGI SAMPAH PLASTIK DI LAUT INDONESIA - Welny Septika P; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research is about the role of Indonesia in realizing Sustainable Development Goals indicator 14, especially in managing marine plastic debris in Indonesian seas. Indonesia is one of the members of the countries in the international organization, United Nations, that have agreed to jointly realize the global ideals of sustainable living. On the other hand, Indonesia is considered as one of the largest contributors of plastic waste to the sea in the world after the publication of scientific papers on research on plastic waste in the sea. This research was developed based on the framework of constructivism perspective that is supported by the theory of national role, as well as the level of analysis using the country, Indonesia, as the main actor. The method of data collection is done by collecting secondary data and then analyzed qualitatively. This research use qualitative descriptive research method. Sources of data was collected by using secondary data such as books, journals, newspapers, magazines, and websites. The results showed that in order to overcome the problem of marine plastic debris in Indonesian seas, Indonesia played role as example and as free and active country. The steps taken in an effort to reduce marine plastic debris are making policies related to sustainable development, educating and socializing 3R (Reduce, Re-use, Recycle) and several programs contained in the National Action Plan (RAN) 2017 – 2025 about handling marine plastic waste, promote and plant mangroves, and attending international meetings discussing marine plastic debris.